AI-enabled smart healthcare using biomedical signals - Chaurasiya, Rahul 1987-; Agrawal, Dheeraj 1979-; Pachori, Ram Bilas 1979- (IGI Global, 2022)
"The book will not only cover the mathematical description of the AI- and ML-based methods; it will also analyze and demonstrate the usability of different AI methods for a range of biomedical signals.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Artificial intelligence -- Medical applications; Signal processing -- Digital techniques; Medical informatics